Pengaruh Profitabilitas dan Market Value Ratio terhadap Harga Saham Bank Umum Syariah - Fajar Rizky Mausuly; Riris Aishah Prasetyowati (Penerbit Goodwood, 2022)
Puprose: The purpose of this study is to explore the relationship between Earnings Per Share, Price to Earnings Ratio and Price to Book Value Ratio on the share prices of Islamic commercial banks. Methodology: This research used quantitative methods to analyze financial data from Islamic commercial banks for the 2021 period. In this study used 4 sharia commercial banks as samples. The analysis was performed using panel data regression analysis using E-views software version 10.0. Results: The results of the study showed that increasing Earnings Per Share (EPS) had a positive effect on stock prices, while the Price to Earnings Ratio (PER) had no significant negative effect, and the Price to Book Value (PBV) had an effect positive but not significant. Meanwhile, simultaneously increasing EPS, PER, and PBV all had a significant effect on stock prices. Contribution: With this research, it is hoped that Islamic banking practitioners and sharia investors will analyse the financial performance of the enterprise before making an investment decision. This esearch also contributes to the development of literature on the factors that influence the share prices of Islamic commercial banks.